Direct and Indirect Climate Change Impacts on Brown Trout in Central Europe: How Thermal Regimes Reinforce Physiological Stress and Support the Emergence of Diseases - Borgwardt, Florian; Unfer, Günther; Auer, Stefan; Waldner, Karoline; El-Matbouli, Mansour; Bechter, Thomas (Frontiers in Environmental Science, 2020)
Water temperature is one of the most important abiotic parameters in rivers having direct and indirect effects on fish. Especially cold-water species like the brown trout (Salmo trutta) are limited by high temperatures. Beside direct physiological stress, higher water temperatures also reinforce the emergence of diseases. In this study we investigate thermal regimes of rivers based on a large-scale dataset covering Austria (approximately 70,000 km²). The analyses aim to clarify to what extent water temperatures support the emergence of proliferative kidney disease (PKD) and assemble physiological stress for brown trout under current and future climate conditions. Data from 274 gauging stations at 184 rivers were used to calibrate a water temperature model and to investigate critical water temperature thresholds. Therefore, we developed a risk assessment scheme to identify river reaches that already have or will develop critical thermal regimes for brown trout in respect of PKD emergence and thermal physiological stress. The results revealed severe changes in the thermal regimes of the investigated rivers under climate change. Furthermore, the variable characterising riparian vegetation played a vital role to explain cooling of the water in downstream direction. In respect of PKD, the amount of river reaches having unlikely outbreaks of PKD decreased from 72.6 % under current conditions to 37.7 % in the far future RCP8.5 scenario. Within small rivers that currently showed optimal thermal regimes over large extents (10,244 km), the habitat suitability will be reduced by combined effects of PKD and physiological stress to 6,554 km. In general, suitable habitats of S. trutta will shift upstream, thus to higher altitudes, and to smaller, alpine rivers in Austria. The warming leads to physiological stress that induces a diminished growth due to the non-positive transition of caloric values to growth as well as cardiac dysfunction in brown trout. These factors will further restrict the distribution of brown trout. However, the results also underline the enormous importance of the alpine region as a future refuge for brown trout in Central Europe. Thus, this study will help to inform managers to timely develop robust conservation strategies.